Sexual and Symbolic Violence: Case Study in Jakarta - Abby Gina Boangmanalu; Gadis Arivia (Jurnal Perempuan, 2016)
This paper examines sexual violence to women in public space. Sexual violence in public space such as in public transportation is quite close to women’s everyday life but frequently ignored due to its invisible impacts. This paper criticizes previous deeds as powerful symbolic violence. This research unearthes that there is strong relation between subjective experiences and other objective structures such as norms and law system in the gender domination hierarchy manifesting in sexual violence.